2016
DOI: 10.1080/19768354.2016.1224204
|View full text |Cite
|
Sign up to set email alerts
|

β-Actin regulates interleukin 6-induced p21 transcription by interacting with the Rpb5 and Rpb7 subunits of RNA polymerase II

Abstract: In pre-initiation complexes, RNA helicase A interacts with β-actin and acts as a bridging factor linking nuclear actin with RNA polymerase II (Pol II). In addition, β-actin participates in Pol IIdependent transcription elongation by interacting with the positive transcription elongation factor Cdk9. However, many relationships between β-actin and Pol II remain to be identified. In an interleukin 6 (IL-6)-induced p21 expression model, we demonstrated that β-actin knockdown reduced p21 expression. Immunofluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition to regulating transcription initiation through transcription factors, actin has also been directly linked to RNA polymerase (Pol) function. Actin co-purifies with all three RNA polymerases [2,[70][71][72] and has been shown to interact with Pol II subunits Rpb5 and Rpb7 [73], as well as Pol III subunits Rpc3, Rpb6 and Rpb8 [72] in co-immunoprecipitation experiments. However, these interactions are poorly understood at the molecular level.…”
Section: Dynamic Nuclear Actin In Gene Expressionmentioning
confidence: 99%
“…In addition to regulating transcription initiation through transcription factors, actin has also been directly linked to RNA polymerase (Pol) function. Actin co-purifies with all three RNA polymerases [2,[70][71][72] and has been shown to interact with Pol II subunits Rpb5 and Rpb7 [73], as well as Pol III subunits Rpc3, Rpb6 and Rpb8 [72] in co-immunoprecipitation experiments. However, these interactions are poorly understood at the molecular level.…”
Section: Dynamic Nuclear Actin In Gene Expressionmentioning
confidence: 99%
“…217 Along with the transcriptional regulation by interacting with other transcription factors, nuclear actin also directly binds to RNA polymerases and regulates their function. It has been reported that actin, specifically β-actin, interacts with Rbp5 and Rbp7 subunits of RNA polymerase II (RNA Pol II) 250 and also Rpb6, Rpb8, and Rpc3 subunits of RNA Pol III. 251 Studies highlighting the function of actin in transcriptional regulation and chromatin dynamics are reviewed in the following references 211,251 ; however, the underlying molecular mechanism is still enigmatic.…”
Section: Mechanical Regulation Of Gene Expressionmentioning
confidence: 99%
“…In the cytoplasm, actin serves a role in cell migration, stress fiber formation, and cell division by forming a contractile ring during cytokinesis. Actin is also present in nuclei, where it plays a crucial role in transcriptional regulation (Vartiainen et al ., 2007; Baarlink et al ., 2013; Tian et al ., 2016; Sokolova et al ., 2018) and in DNA damage repair processes (Chiolo et al ., 2011; Belin et al ., 2015; Caridi et al ., 2019). Actin nuclear localization is mediated through the interplay of nuclear import regulated by importin 9 with cofilin (Dopie et al ., 2012) and nuclear export regulated by exportin 6 (Exp6), which transports profilin-actin complexes (Stüven et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%